2018
DOI: 10.17116/stomat20189704119
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of oral diseases in pregnant women

Abstract: The prevalence of tooth caries and periodontitis in pregnant women has been studied; susceptibility of pregnant women to a high risk of development of dental pathology. Proven factors that modify the risk of tooth caries, periodontitis of mild and moderate severity in pregnancy are age over 30 years, repeated childbirth and pregnancy, complications of the gestational period, and for periodontitis, additionally - diseases of the digestive system, musculoskeletal system , anemia and metabolic-endocrine disorders. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…In China none of the investigated factors were associated with women of childbearing age, and self-reported bleeding during tooth brushing was the only factor associated with periodontal disease [adjusted odds ratio (aOR): 3.71] [21]. A previous study showed that age (over 30 years) and high parity were associated with periodontal disease during pregnancy [14]. Moreover, higher maternal age and parity were reported to be associated with periodontal disease during pregnancy in Uganda [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China none of the investigated factors were associated with women of childbearing age, and self-reported bleeding during tooth brushing was the only factor associated with periodontal disease [adjusted odds ratio (aOR): 3.71] [21]. A previous study showed that age (over 30 years) and high parity were associated with periodontal disease during pregnancy [14]. Moreover, higher maternal age and parity were reported to be associated with periodontal disease during pregnancy in Uganda [25].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of periodontal disease among pregnant women varies in different populations [11][12][13]. Moreover, several factors such as age, parity, lower level of education and anaemia were identified as risk factors for periodontal disease during pregnancy [4,14]. While there is a large amount of data on periodontal disease during pregnancy in other African countries [12,15,16], there is no data on periodontal disease during pregnancy in Sudan.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, another study reported; older age, a lower level of education, and unemployment were factors associated with periodontal disease in pregnant women [32]. A previous study showed that age (over 30 years) and high parity were associated with periodontal disease during pregnancy [33]. Also, In Uganda higher maternal age and parity were reported to be associated with periodontal disease during pregnancy [34].…”
Section: Discussionmentioning
confidence: 99%
“…There are different contributing factors, such as age, parity, lower level of education, and anemia were identified as risk factors for periodontal disease. 32 Moreover, poor oral hygiene, 33 smoking, 33–35 ethnicities, 1 , 3 body mass index, bacterial plaque, 10 lower gestational age, 17 residency, systemic disease, 18 psychosocial factors (depression, anxiety, and stress), 36 , 37 and poor economic status 1 , 3 , 38–40 have been reported as risk factors for periodontal disease. Due to different factors, PD is complicated with tooth loss which can compromise intake of food, aesthetics, self-confidence, and quality of life.…”
Section: Introductionmentioning
confidence: 99%